2010
DOI: 10.1093/jnci/djq214
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Cancer Mortality of Workers Exposed to Aromatic Amines: A 58-Year Follow-up

Abstract: We previously investigated bladder cancer risk in a cohort of dyestuff workers who were heavily exposed to aromatic amines from 1922 through 1972. We updated the follow-up by 14 years (through 2003) for 590 exposed workers to include more than 30 years of follow-up since last exposure to aromatic amines. Expected numbers of deaths from bladder cancer and other causes were computed by use of national mortality rates from 1951 to 1980 and regional mortality rates subsequently. There were 394 deaths, compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 14 publications
2
35
0
2
Order By: Relevance
“…Occupational exposure to aromatic amines has long been recognized a risk factor for bladder cancer (Negri et al, 1989;Kogevinas et al, 2003;Bosetti et al, 2005;Pira et al, 2010;Pira et al, 2012), accounting for up to 15% of cases in men from selected high-risk populations D'Avanzo et al, 1995). However, a selected number of occupations a priori deemed as being of high risk for bladder cancer showed only a moderate, nonsignificant excess risk, indicating that occupational exposures are not a major factor for bladder cancer in this, mainly rural, population.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure to aromatic amines has long been recognized a risk factor for bladder cancer (Negri et al, 1989;Kogevinas et al, 2003;Bosetti et al, 2005;Pira et al, 2010;Pira et al, 2012), accounting for up to 15% of cases in men from selected high-risk populations D'Avanzo et al, 1995). However, a selected number of occupations a priori deemed as being of high risk for bladder cancer showed only a moderate, nonsignificant excess risk, indicating that occupational exposures are not a major factor for bladder cancer in this, mainly rural, population.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer is much more common in males and is typically diagnosed at a median age of 70 years [1,2]. Environmental exposures, whether to occupational carcinogens or cigarette smoke, account for most cases of bladder cancer [3,4]. The spectrum of bladder cancer includes nonmuscle-invasive (superficial), muscle-invasive, and metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Medical research during the last decades has identified the risk factors inducing bladder cancer: age [11], gender [12], family history of BC [13], smoking [14,15,16], occupational risk [17,18,19,20,21,22] and medical risk [23,24]. …”
Section: Discussionmentioning
confidence: 99%